SAMIR a tool for irrigation monitoring using remote sensing for evapotranspiration estimate - Lepage M.; Simonneaux V.; Thomas S.; Metral J.; Duchemin B.; Kharrou H.; Cherkaoui M.; Chehbouni A. (Technological perspectives for rational use of water resources in the Mediterranean region, 2009)
SAMIR is software computing spatialized estimates of evapotranspiration (ET) and irrigation water budget on large areas, based on the use of satellite images. Remote sensing offers a synoptic view of the vegetation development, which is a key information for ET reliable computing. ET is obtained using the FAO method, well suited for computation over large areas, where little information is usually available about crops and soils. The computation of the water budget requires climatic data (reference ET - namely ET0 - and rainfall data), land cover data, and crop development data (for estimating crop coefficients of the FAO method), these last two types of data being obtained from remote sensing. Irrigation may be an input when it is known, but it is most of the time estimated from the computation of the water budget, using hypotheses on the water management modes and especially the average water stress level allowed. The irrigation estimates at the scale of irrigation sectors may be compared with known water inputs from dams and traditional seguias (traditional channels deriving water from rivers) to estimate pumpings in the aquifer. In a context of strong pressure applied on water resources, we emphasize the potential of satellite images for irrigation monitoring and water management at watershed scale.
2. MELIA Workshop Technological Perspectives for Rational Use of Water Resources in the Mediterranean Region, 2008/10/29-2008/11/02, Marrakesh (Morocco)